New Insights Into the Reservoir Landslide Deformation Mechanism From InSAR and Numerical Simulation Technology - Guoshi Liu; Bin Wang; Qian Sun; Jun Hu; Lei-Lei Liu; Wanji Zheng; Liye Zou (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Reservoir landslides represent a significant geological hazard that jeopardizes the safety of reservoirs. Deformation monitoring and numerical simulation are essential methodologies for elucidating the evolutionary patterns of landslides. Nonetheless, the existing approaches exhibit limitations in revealing the potential deformation mechanism. Consequently, this study proposes an innovative strategy that incorporates interferometric synthetic aperture radar (InSAR) deformation characteristics alongside fluid–solid coupling stress analysis to investigate the deformation, focusing on the Shuizhuyuan landslide within the Three Gorges Reservoir area as a case study. Using temporary coherence point InSAR technology, significant motion units were identified, with a maximum deformation rate of −60 mm/yr. The complete deformation time series reveals three independent components of landslide movement and their trigger factors geometrically. Subsequently, the saturation permeability coefficient of the sliding mass in the seepage analysis is modified with the assistance of InSAR deformation. Then, we coupled the seepage analysis results to FLAC3D model for stress and strain analysis, and determined the seepage-induced progressive failure mechanism and the deformation mode of the Shuizhuyuan landslide, driven by reservoir water-level (RWL) drop. The numerical simulation results aid in interpreting the deformation mechanism of different spatial and temporal patterns of landslides from three aspects: hydrodynamic pressure from rainfall infiltration, groundwater hysteresis caused by RWL drop, and seepage forces from RWL rise. Furthermore, our findings reveal that the dynamic factor of safety (FOS) of landslide during the InSAR observation period is highly consistent with the periodic fluctuations of the RWL. However, there is also a small trend of overall decline in FOS that cannot be ignored.